Desempenho e emissões de um motor de trator agrícola operando com misturas de óleo diesel e etanol - Estrada, Javier Solis (2015)
The growing demand of energy in the world, the decrease of petroleum reserves and the current problems of environmental contamination, increase the interest in renewable energy study for internal combustion engines, to replace partially or completely to petroleum based fuels. In Brazil, among the alternatives fuels, stands out the use of sugarcane ethanol, seen that it is from renewable sources and has high oxygen content, which is favorable to reduce pollutant gases emissions of engine. The blend of ethanol and diesel (ED) has received in recent years and in different countries, more attention for use in diesel engines. However, there are difficulties to partially replace diesel use. The main disadvantages are the differences in their physical-chemical properties. A percentage up to 15% of ethanol is used in diesel engines without making mechanical changes. In this way, the objective of this study was to evaluate the performance and emissions of a diesel engine in an agricultural tractor, using blends of diesel and hydrated ethanol. Were used as fuel, Diesel (B5) and mixture with 3% (ED3), 6% (ED6), 9% (ED9), 12% (ED12) and 15% (ED15) of hydrous ethanol. Performance parameters evaluated were the power, torque and specific fuel consumption. Were also evaluated emissions of CO2, NOx e O2, and the opacity of the gases through the k value. Both, engine performance and emissions experiment were analyzed in a completely randomized with bifactorial design. The results indicate that as the percentage of ethanol increased, the average values of torque and engine power decreased. Using the B5 and the ED3, these variables did not differ statistically, in addition, with the ED3 was obtained the lower specific fuel consumption. Using ED12, the engine performance has reduced power and torque in 2.97% e 2.95%, respectively, compared with B5, while their fuel consumption had no statistical difference. The greater opacity and gas emissions were archive with ED3, while the lower emission occurred when the engine operated with ED12 and ED15. With these fuels, the reduction of opacity, CO2 and NOX, in relation to B5, was 22.22 24.44%, 5.20 5.60% e 6.65 - 10.48%, respectively. It can be considerate that operating with ED12, pollutant emissions are reduced significantly without a significant loss in engine performance.